2013
DOI: 10.1159/000354871
|View full text |Cite
|
Sign up to set email alerts
|

High Evolutionary Dynamism in 5S rDNA of Fish: State of the Art

Abstract: The 5S ribosomal DNA (rDNA) consists of one transcriptional unit of about 120 base pairs, which is separated from the next unit by a non-transcribed spacer (NTS). The coding sequence and the NTS together form a repeat unit which can be found in hundreds to thousands of copies tandemly repeated in the genomes. The NTS regions seem to be subject to rapid evolution. The first general model of evolution of these multigene families was referred to as divergent evolution, based on studies using hemoglobin and myoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 69 publications
(103 reference statements)
3
55
0
Order By: Relevance
“…Additionally, the absence and presence of Mutsu retrotransposon RNA and piRNA in eggs, respectively, together with the reversed situation in adult tissue, fuel the need to investigate the obvious link between 5S rRNA and these sequence-specific non-LTR retrotransposons. All of this sparks the notion that the retrotransposon elements are involved in the way the copy numbers evolved in both maternal-and somatic-type 5S rDNA loci (Rebordinos et al 2013), similar to that reported in 45S (Symonová et al 2013).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Additionally, the absence and presence of Mutsu retrotransposon RNA and piRNA in eggs, respectively, together with the reversed situation in adult tissue, fuel the need to investigate the obvious link between 5S rRNA and these sequence-specific non-LTR retrotransposons. All of this sparks the notion that the retrotransposon elements are involved in the way the copy numbers evolved in both maternal-and somatic-type 5S rDNA loci (Rebordinos et al 2013), similar to that reported in 45S (Symonová et al 2013).…”
Section: Resultssupporting
confidence: 58%
“…If we assume that two intact ORFs equals a functional retrotransposon element, it is an intriguing observation that apparently in the locus with many (maternal-type) 5S rRNA genes, several potentially active retrotransposons reside, whereas in the small (somatic-type) locus there is none. It raises the question whether these retrotransposons were evolutionarily involved in achieving and maintaining the needed high maternal-type 5S rDNA gene copy number, as well as the limited somatictype 5S rRNA gene copy (Cioffi et al 2010;Rebordinos et al 2013). In this scenario, one function of the sequence difference between maternal-and somatic-type 5S rRNA genes could be that the different target sequence in the somatictype genes obstructs new integration of retrotransposons, thus stabilizing the somatic-type 5S rRNA locus.…”
Section: Linking 5s Rrna Variants To Different Members Of the Retrotrmentioning
confidence: 99%
“…Thus, presence of other multigene families (LINES, SINES, non-LTR retrotransposons), especially regarding the NTSs, appears to be suitable among fish. These multigene families seems to collaborate with variability in this region (seem review Rebordinos et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomal RNA genes are among the best known multigene families in vertebrates, and the molecular variability of the 5S rDNA has been elucidated frequently according to NTS, which are normally associated with other repetitive DNA [Campo and García-Vázquez, 2012;Rebordinos et al, 2013]. In the species Cnemidophorus sp.…”
Section: Discussionmentioning
confidence: 99%